Centrifugal ultra-high performance concrete pole and production process thereof
By improving the raw material formula and production process of concrete poles and using centrifugal process to prepare ultra-high performance concrete poles, solving the limitations of traditional concrete poles in terms of bearing capacity, crack resistance and durability, and achieving significant mechanical properties and crack resistance improvements.
Patent Information
- Application Number
- CN202510111607.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional concrete poles have limitations in bearing capacity, crack resistance and durability, and are difficult to meet increasingly demanding application conditions.
By improving the raw material formula, raw material ratio and production process, centrifugal ultra-high performance concrete poles are prepared by mixing cement, quartz sand, silicon powder, steel fiber, polyvinyl alcohol fiber, polypropylene fiber, water reducing agent and water in a specific proportion, and treated by centrifugation and curing process.
It significantly improves the mechanical properties and crack resistance of concrete poles, enhances stability and service life in harsh environments, while reducing weight and reducing maintenance costs.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cement pole production, and in particular relates to a centrifugal ultra-high performance concrete pole and a production process thereof. Background Art
[0002] Concrete poles are infrastructure components widely used in fields such as electricity, communications and transportation. They usually bear various static and dynamic loads, such as wind pressure, deadweight, temperature changes, etc., and therefore have strict requirements on mechanical properties and durability.
[0003] In terms of mechanical properties, according to different concrete pole proportions and production processes, the 28-day compressive strength of concrete poles produced by existing manufacturers is usually between 30MPa and 60MPa, the 28-day tensile strength is usually between 3MPa and 5MPa, and the 28-day flexural strength is generally between 10MPa and 15MPa; in terms of anti-cracking performance, according to GB / T 4623-2014 standard, the crack resistance coefficients of prestressed concrete poles and partially prestressed concrete poles are 1.0 and 0.8 respectively.
[0004] With the development of technology and increasingly stringent application conditions, traditional concrete poles have gradually shown limitations in bearing capacity, crack resistance and durability. Therefore, it is necessary to further improve the mechanical properties and anti-cracking performance of concrete poles. Summary of the invention
[0005] The present application aims to further optimize and enhance the mechanical properties and anti-cracking performance of concrete rods by improving the raw material formula, raw material ratio and production process on the basis of the existing technology, which can not only enhance its stability and service life in harsh environments, but also reduce maintenance costs and avoid safety accidents caused by structural failure. To this end, the present invention provides a centrifugal ultra-high performance concrete rod and its production process.
[0006] The purpose of the present invention can be achieved through the following technical solutions: A centrifugal ultra-high performance concrete rod comprises the following raw materials in parts by weight: 700-720 parts of cement, 1150-1200 parts of quartz sand, 230-250 parts of silica powder, 120-150 parts of steel fiber, 0-3 parts of polyvinyl alcohol fiber, 0-1.2 parts of polypropylene fiber, 20 parts of water reducer, and 210 parts of water; the quartz sand is one of quartz sand I, quartz sand II, and quartz sand III with different particle size ranges or a mixture of quartz sand I, quartz sand II, and quartz sand III in a mass ratio of 4:3:3; the steel fiber is copper-plated microfilament steel fiber; and the polypropylene fiber is polypropylene monofilament fiber.
[0007] Furthermore, the cement is ordinary Portland cement with code name P·O52.5.
[0008] Furthermore, the quartz sand is composed of one of quartz sand I, quartz sand II, and quartz sand III with different particle size ranges or a mixture of quartz sand I, quartz sand II, and quartz sand III in a mass ratio of 4:3:3.
[0009] Furthermore, the particle size range of the quartz sand I is 0.60 mm to 1.1 mm; the particle size range of the quartz sand II is 0.35 mm to 0.60 mm; and the particle size range of the quartz sand III is 0.20 mm to 0.35 mm.
[0010] Furthermore, the silicon content of the silicon powder is ≥95%.
[0011] Furthermore, the length of the copper-plated microfilament steel fiber is 12 mm to 14 mm, and the diameter is 0.18 mm to 0.20 mm.
[0012] Furthermore, the length of the polyvinyl alcohol fiber is 12 mm to 14 mm, and the diameter is 0.20 mm to 0.22 mm.
[0013] Furthermore, the production process of the centrifugal ultra-high performance concrete rod comprises the following steps: S1. Weigh each raw material according to mass parts, first put quartz sand, steel fiber, polyvinyl alcohol fiber and polypropylene fiber into a mixer, stir for 150-200 seconds, then add cement and silicon powder thereto in sequence, stir for 120-150 seconds, then add water and water reducing agent thereto in sequence, stir for 200-250 seconds, after stirring, obtain a concrete mixture, and place the concrete mixture in a feeder for standby use; S2, applying mold release silicone oil to the concrete rod mold, adding a steel skeleton, adding a 304 stainless steel wire mesh to the steel skeleton, and then using a tensioning machine to pre-tension the steel skeleton, and then pouring the concrete mixture in the feeder evenly into the concrete rod mold. After adding, clean the mold periphery and close the mold to obtain a loading mold; S3. Place the loading mold on a centrifuge, set the speed to 100-150r / min, centrifuge for 90-100s, then increase the speed to 200-400r / min, centrifuge for 50-60s, then increase the speed to 600-800r / min, centrifuge for 480-500s, let it stand for 20-30min after centrifugation, and then transfer it to a steam curing tank for steam curing. During the steam curing process, the heating rate is adjusted to 15℃ / h. When the ambient temperature rises from room temperature to 90℃, it is cured at a constant temperature for 8-10h. After curing, it is cooled to room temperature at a cooling rate of 15℃ / h, and then demolded and watered to obtain a centrifugal ultra-high performance concrete rod.
[0014] Furthermore, the steel bar skeleton includes steel bars, spiral bars, protective layer washers and stand rings; the steel bars are steel bars for prestressed concrete; the spiral bars and stand rings are made of cold-drawn low-carbon steel wire; and the protective layer washers are made of polystyrene.
[0015] Beneficial effects of the present invention: The present invention obtains a centrifugal ultra-high performance concrete rod by mixing cement, quartz sand, silicon powder, steel fiber, polyvinyl alcohol fiber, polypropylene fiber, a water reducer and water in a certain proportion, and then centrifuging and curing. Compared with the prior art, the present invention relatively reduces the amount of cement in the concrete rod by adding additives such as steel fiber, polyvinyl alcohol fiber and polypropylene fiber, which helps to reduce the weight of the concrete rod. More importantly, the mechanical properties and crack resistance of the concrete rod are significantly improved.
[0016] Then, the present invention expands the contact area between concrete and the steel skeleton by adding a steel mesh made of 304 stainless steel into the steel skeleton, which helps to improve the crack resistance of the prepared concrete rod and also effectively solves the technical problem that the concrete rod is easy to collapse after centrifugation. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] Firstly, the present invention provides a centrifugal ultra-high performance concrete rod, comprising the following raw materials in parts by weight: 700-720 parts of cement, 1150-1200 parts of quartz sand, 230-250 parts of silicon powder, 120-150 parts of steel fiber, 0-3 parts of polyvinyl alcohol fiber, 0-1.2 parts of polypropylene fiber, 20 parts of water reducer, and 210 parts of water. Wherein, the cement is ordinary Portland cement with the code name P·O52.5, and the quality of the cement meets the relevant provisions of GB175-2023; wherein, the quartz sand is composed of one of quartz sand I, quartz sand II, and quartz sand III with different particle size ranges or quartz sand I, quartz sand II, and quartz sand III are mixed in a mass ratio of 4:3:3, the particle size range of quartz sand I is 0.60mm~1.1mm, the particle size range of quartz sand II is 0.35mm~0.60mm, the particle size range of quartz sand III is 0.20mm~0.35mm, and the quality of quartz sand meets the relevant provisions of JGJ52-92; wherein, the silicon content of silicon powder is ≥95%, and after testing, the silicon content of the raw silicon powder in the present invention is 95.4%, and the quality of silicon powder meets GB / T 27690-2023; wherein the steel fiber is a copper-plated microfilament steel fiber, the length of the copper-plated microfilament steel fiber can be 12mm-14mm, and the diameter can be 0.18mm-0.20mm. The length of the raw material copper-plated microfilament steel fiber in the present invention is 13mm, the diameter is 0.20mm, and the quality of the copper-plated microfilament steel fiber meets the relevant provisions in GB / T 31387-2015; wherein the length of the polyvinyl alcohol fiber can be 12mm-14mm, and the diameter can be 0.20mm-0.22mm. The length of the raw material polyvinyl alcohol fiber in the present invention is 13mm, the diameter is 0.22mm, and the quality of the polyvinyl alcohol fiber meets the relevant provisions in GB / T 12010.3-2010; wherein the polypropylene fiber is a polypropylene monofilament fiber, and the quality of the polypropylene monofilament fiber meets the relevant provisions in JT / T 525-2004; wherein the water reducer is a VIS3301 polycarboxylic acid water reducer of SIKA Company of Switzerland.
[0019] Then, the present invention discloses a production process of a centrifugal ultra-high performance concrete rod, the steps of which are as follows: S1. Weigh the raw materials according to the above-mentioned parts by mass. First, put quartz sand, steel fiber, polyvinyl alcohol fiber and polypropylene fiber into a mixer and stir for 150 to 200 seconds, or 150 seconds in the present invention. Then, cement and silicon powder are sequentially added thereto and stirred for 120 to 150 seconds, or 120 seconds in the present invention. Then, water and a water reducing agent are sequentially added thereto and stirred for 200 to 250 seconds, or 200 seconds in the present invention. After stirring, a concrete mixture is obtained, and the concrete mixture is placed in a feeder for standby use.
[0020] S2. Apply silicone oil as a release agent to the concrete rod mold, add a steel skeleton thereto, add a wire mesh made of 304 stainless steel to the steel skeleton, use a tensioning machine to pre-tension the steel skeleton, and then evenly pour the concrete mixture in the feeder into the concrete rod mold. After the addition is completed, clean the mold periphery and close the mold to obtain a loading mold, wherein the steel skeleton includes steel bars, spiral bars, protective layer washers and stand rings, the steel bars can be hot-rolled ribbed steel bars or prestressed concrete steel bars, both of which are weldable, the quality of the hot-rolled ribbed steel bars meets the relevant provisions of GB 1499.2-2024, the quality of the prestressed concrete steel bars meets the relevant provisions of GB / T 5223.3-2017, and the present invention specifically uses prestressed concrete steel bars; wherein the spiral bars and the stand rings are made of cold-drawn low-carbon steel wires, and their quality meets the relevant provisions of JC / T 540-2006; wherein the protective layer washers are made of polystyrene.
[0021] S3. Place the loading mold on a centrifuge, set the speed to 100 r / min, centrifuge for 90 seconds, then increase the speed to 200 r / min, centrifuge for 60 seconds, then increase the speed to 600 r / min, centrifuge for 480 seconds, let it stand for 20 minutes after centrifugation, and then transfer it to a steam curing tank for steam curing. During the steam curing process, the heating rate is adjusted to 15°C / h. When the ambient temperature rises from room temperature to 90°C, it is cured at a constant temperature for 8 hours. After curing, it is cooled to room temperature at a cooling rate of 15°C / h, and then demolded and watered to obtain a centrifugal ultra-high performance concrete rod.
[0022] Example 1 to Example 14 Embodiments 1 to 14 specifically disclose a production process of a centrifugal ultra-high performance concrete rod. The specific production steps are the same as above. The specific raw material formula of the concrete rod is shown in Table 1 below: Table 1 Raw material formula of concrete poles of Example 1 to Example 14 (parts by mass) Example No. cement Quartz sand Quartz sand ratio (Ⅰ:Ⅱ:Ⅲ) Silicon powder Steel Fiber Polyvinyl alcohol fiber Polypropylene fiber Water reducing agent water 1 700 1200 4:3:3 250 120 2 1.2 20 210 2 700 1200 10:0:0 250 120 2 1.2 20 210 3 700 1200 0:10:0 250 120 2 1.2 20 210 4 700 1200 0:0:10 250 120 2 1.2 20 210 5 700 1200 4:3:3 250 120 0 0 20 210 6 700 1200 4:3:3 250 120 1 1.2 20 210 7 700 1200 4:3:3 250 120 3 1.2 20 210 8 720 1150 4:3:3 230 150 2 1.2 20 210 9 720 1150 10:0:0 230 150 2 1.2 20 210 10 720 1150 0:10:0 230 150 2 1.2 20 210 11 720 1150 0:0:10 230 150 2 1.2 20 210 12 720 1150 4:3:3 230 150 0 0 20 210 13 720 1150 4:3:3 230 150 1 1.2 20 210 14 720 1150 4:3:3 230 150 3 1.2 20 210 Comparative Example 1 Comparative Example 1: Ordinary concrete is used to prepare concrete rods, and the formula by mass is as follows: 350 parts of cement, 530 parts of river sand, 950 parts of crushed stone, 8 parts of water reducer, and 162 parts of water, wherein the cement is ordinary Portland cement code-named P·O52.5, and the quality of the cement meets the relevant provisions of GB175-2023; wherein the particle size of the river sand is 0.25 mm to 2 mm; the particle size of the crushed stone is 5 mm to 20 mm; and the water reducer is VIS3301 polycarboxylate water reducer of SIKA Company of Switzerland.
[0023] The production process of the concrete pole in Comparative Example 1 comprises the following steps: S1. Weigh the raw materials according to the above mass parts. First, put cement, river sand and crushed stone into a mixer and stir for 5 minutes. Then add water and water reducing agent thereto in sequence and stir for 4 minutes. After stirring, a concrete mixture is obtained. The concrete mixture is placed in a feeder for standby use.
[0024] S2. Apply release agent silicone oil to the concrete rod mold, add a steel bar skeleton thereto, and then use a tensioning machine to pre-tension the steel bar skeleton, and then evenly pour the concrete mixture in the feeder into the concrete rod mold. After the addition is completed, clean the mold periphery and close the mold to obtain a loading mold, wherein the steel bar skeleton includes steel bars, spiral bars, protective layer washers and stand rings, the steel bars can be hot-rolled ribbed steel bars or prestressed concrete steel bars, both of which are weldable, the quality of the hot-rolled ribbed steel bars meets the relevant provisions of GB 1499.2-2024, the quality of the prestressed concrete steel bars meets the relevant provisions of GB / T 5223.3-2017, and the present invention specifically uses prestressed concrete steel bars; wherein the spiral bars and the stand rings are made of cold-drawn low-carbon steel wires, and their quality meets the relevant provisions of JC / T 540-2006; wherein the protective layer washers are made of polystyrene.
[0025] S3. Place the loading mold on a centrifuge, set the speed to 100r / min, centrifuge for 90s, then increase the speed to 200r / min, centrifuge for 60s, then increase the speed to 600r / min, centrifuge for 480s, let it stand for 20min after centrifugation, and then transfer it to a steam curing tank for steam curing. During the steam curing process, the heating rate is adjusted to 15℃ / h. When the ambient temperature rises from room temperature to 90℃, it is cured at a constant temperature for 8h. After curing, it is cooled to room temperature at a cooling rate of 15℃ / h, and then demolded and watered to obtain a concrete pole.
[0026] Test Example 1 The standard test blocks of 100 mm × 100 mm × 100 mm were produced according to the raw material formulas in Examples 1 to 14 and Comparative Example 1, respectively. The compressive strength, tensile strength and flexural strength of the standard test blocks after curing for 28 days under standard oxidation conditions were determined with reference to the test standards in GB / T 50081-2019. The test results are shown in Table 2 below: Table 2 Standard test block test results (MPa) Serial number 28 days compressive strength 28-day tensile strength 28-day flexural strength Example 1 136.4 8.5 18.1 Example 2 125.1 7.8 17.2 Example 3 131.5 8.1 16.8 Example 4 128.6 8.0 16.5 Example 5 124.2 7.6 15.8 Example 6 133.3 8.3 17.5 Example 7 130.1 8.1 16.6 Example 8 141.2 8.8 18.6 Example 9 129.7 8.0 16.3 Example 10 135.4 8.4 17.8 Embodiment 11 132.3 8.2 16.9 Example 12 129.8 8.0 16.1 Embodiment 13 136.5 8.5 17.9 Embodiment 14 133.3 8.3 17.4 Comparative Example 1 59.7 6.4 7.7 By studying the data in Table 2, we can draw the following conclusions: (1) By comparing the data of Example 1, Example 2, Example 3, Example 4 or Example 8, Example 9, Example 10, and Example 11 in Table 2, it can be obtained that when quartz sands with three different particle size ranges and gradient particle size distribution are used, the strength of the standard test blocks produced is higher than the strength of the standard test blocks produced when quartz sands with a single particle size range are used, that is, the grading of quartz sand is beneficial to improving the strength of concrete.
[0027] (2) By comparing the data of Example 1, Example 6, Example 7 or Example 8, Example 13, and Example 14 in Table 2, it can be obtained that when the amount of polyvinyl alcohol fiber is changed and the other proportions are kept consistent, the strength of the produced standard test block first increases and then decreases. Therefore, when mixing ultra-high performance concrete, the fiber content should be strictly controlled and should not be too high or too low.
[0028] (3) In summary, the strength of the standard test blocks produced using the ultra-high performance concrete formulas given in Examples 1 to 14 of the present invention is greater than the strength of the standard test blocks produced using the ordinary concrete formula.
[0029] Test Example 2 The centrifugal ultra-high performance concrete rods / concrete rods with the same size produced by the same loading mold prepared in Examples 1 to 14 and Comparative Example 1 were subjected to mechanical property tests and appearance inspections, wherein the deflection, crack resistance coefficient and deflection crack width refer to the test standards in GB4623-2014, and the test results are shown in Table 3 below: Table 3 Mechanical properties test and appearance test results Serial number 100% deflection(mm) 200% deflection(mm) Crack resistance coefficient 200% deflection crack width (mm) Shaft appearance Example 1 186.9 489.7 1.45 0.08 Unbroken Example 2 173.1 470.9 1.51 0.07 Unbroken Example 3 182.6 503.9 1.38 0.10 Unbroken Example 4 177.9 486.3 1.53 0.06 Unbroken Example 5 171.4 481.2 1.57 0.06 Unbroken Example 6 182.1 496.5 1.48 0.08 Unbroken Example 7 179.6 486.6 1.50 0.08 Unbroken Example 8 196.7 511.3 1.35 0.06 Unbroken Example 9 182.6 491.7 1.43 0.07 Unbroken Example 10 189.3 502.6 1.39 0.08 Unbroken Embodiment 11 184.8 499.1 1.41 0.08 Unbroken Example 12 177.5 485.6 1.47 0.06 Unbroken Embodiment 13 188.4 495.1 1.40 0.08 Unbroken Embodiment 14 181.2 480.4 1.46 0.06 Unbroken Comparative Example 1 261.6 638.9 1.00 0.22 Unbroken By studying the data in Table 3, we can draw the following conclusions: The centrifugal ultra-high performance concrete rods produced in Examples 1 to 14 of the present invention are significantly superior to ordinary concrete rods in terms of mechanical properties and crack resistance coefficient. At the same time, it was found during the research process that adding a wire mesh to the inside of the steel skeleton can be more conducive to the centrifugal forming of ultra-high performance concrete.
[0030] It should be noted that, in this article, terms such as "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment.
[0031] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A centrifugal ultra-high performance concrete rod, characterized in that: Including the following raw materials by weight: 700-720 parts of cement, 1150-1200 parts of quartz sand, 230-250 parts of silica powder, 120-150 parts of steel fiber, 0-3 parts of polyvinyl alcohol fiber, 0-1.2 parts of polypropylene fiber, 20 parts of water reducer, and 210 parts of water; the quartz sand is one of quartz sand I, quartz sand II, and quartz sand III with different particle size ranges or a mixture of quartz sand I, quartz sand II, and quartz sand III in a mass ratio of 4:3:3; the steel fiber is copper-plated microfilament steel fiber; and the polypropylene fiber is polypropylene monofilament fiber.
2. A centrifugal ultra-high performance concrete rod according to claim 1, characterized in that: The cement is ordinary Portland cement with code name P·O52.
5.
3. The centrifugal ultra-high performance concrete rod according to claim 1, characterized in that: The quartz sand is composed of one of quartz sand I, quartz sand II, and quartz sand III with different particle size ranges or a mixture of quartz sand I, quartz sand II, and quartz sand III in a mass ratio of 4:3:
3.
4. A centrifugal ultra-high performance concrete rod according to claim 3, characterized in that: The particle size range of the quartz sand I is 0.60 mm to 1.1 mm; the particle size range of the quartz sand II is 0.35 mm to 0.60 mm; and the particle size range of the quartz sand III is 0.20 mm to 0.35 mm.
5. The centrifugal ultra-high performance concrete rod according to claim 1, characterized in that: The silicon content of the silicon powder is ≥95%.
6. The centrifugal ultra-high performance concrete rod according to claim 1, characterized in that: The length of the copper-plated microfilament steel fiber is 12 mm to 14 mm, and the diameter is 0.18 mm to 0.20 mm.
7. The centrifugal ultra-high performance concrete rod according to claim 1, characterized in that: The length of the polyvinyl alcohol fiber is 12 mm to 14 mm, and the diameter is 0.20 mm to 0.22 mm.
8. A production process for centrifugal ultra-high performance concrete rods according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Weigh each raw material according to mass parts, first put quartz sand, steel fiber, polyvinyl alcohol fiber and polypropylene fiber into a mixer, stir for 150-200 seconds, then add cement and silicon powder thereto in sequence, stir for 120-150 seconds, then add water and water reducing agent thereto in sequence, stir for 200-250 seconds, after stirring, obtain a concrete mixture, and place the concrete mixture in a feeder for standby use; S2, applying mold release silicone oil to the concrete rod mold, adding a steel skeleton, adding a 304 stainless steel wire mesh to the steel skeleton, and then using a tensioning machine to pre-tension the steel skeleton, and then pouring the concrete mixture in the feeder evenly into the concrete rod mold. After adding, clean the mold periphery and close the mold to obtain a loading mold; S3. Place the loading mold on a centrifuge, set the speed to 100-150r / min, centrifuge for 90-100s, then increase the speed to 200-400r / min, centrifuge for 50-60s, then increase the speed to 600-800r / min, centrifuge for 480-500s, let it stand for 20-30min after centrifugation, and then transfer it to a steam curing tank for steam curing. During the steam curing process, the heating rate is adjusted to 15℃ / h. When the ambient temperature rises from room temperature to 90℃, it is cured at a constant temperature for 8-10h. After curing, it is cooled to room temperature at a cooling rate of 15℃ / h, and then demolded and watered to obtain a centrifugal ultra-high performance concrete rod.
9. The production process of a centrifugal ultra-high performance concrete rod according to claim 8, characterized in that: The steel bar skeleton comprises steel bars, spiral bars, protective layer washers and stand rings; the steel bars are steel bars for prestressed concrete; the spiral bars and stand rings are made of cold-drawn low-carbon steel wires; and the protective layer washers are made of polystyrene.